Przywództwo polityczne I sekretarzy w okresie realnego socjalizmu (Politeja, 2022)
POLITICAL LEADERSHIP OF THE FIRST SECRETARIES IN THE PERIOD OF REAL SOCIALISMThe subject of the analysis is the issue of the political leadership of the leaders of communist parties in the countries of Central and Eastern Europe. Formed and functioning political systems were characterized by an undemocratic and centralized internal character. Although the degree of repressiveness of the system evolved and changed (from the condemnation of crimes and the so-called distortion of Stalinism), the above features characterized the analyzed countries until the end of the 1980s, becoming an inherent element of the power system. In the discussed context, the states of the region in question (except for Yugoslavia after 1948 and Albania after 1961) remained in the so-called In the Soviet sphere of influence, external factors are an important element of leadership, i.e. the degree of dependence (or autonomy) of bloc politicians from the Kremlin and politicians from the leadership of the USSR.